KEMAMPUAN ANTAGONIS BAKTERI ENDOFIT ASAL TANAMAN SAGU (Metroxylon spp) DALAM MENEKAN PERTUMBUHAN Rhizoctonia solani Kuhn. SECARA IN VITRO - Ch. Leiwakabessy; Yatni Yatni; C. Uruilal; R. E. Ririhena; F. J. Rumalatu (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
Endophytic bacteria is microbe lives in plant tissues without causing symptoms of disease. The benefit of utilizing endophytic bacteria as a technique for controlling diseases such as sprout (R. solani) has been known due to its ability to live and to colonize plant internal tissues. This study aims to determine the ability of endophytic bacteria from sago to suppress the growth of R. solani in vitro. This research was conducted using 19 isolates of endophytic bacteria from sago with 5 replications. The results showed that two endophytic isolates namely STA2 and STA13 were able to suppress the growth of R. solani pathogens compared to controls with inhibition percentage of 41.86% and 16.27%, respectively.